1995
DOI: 10.1139/v95-258
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystallization in random copolymers of poly(β-hydroxybutyrate-co-β-hydroxyvalerate) and its effect on crystalline morphology

Abstract: Small-angle X-ray scattering (SAXS) and solid state CPMAS I3c NMR were used to describe the crystalline morphology of a series of bacterially produced poly((3-hydroxybutyrate-co-P-hydroxyvalerate) copolymers containing random distributions of 3-hydroxybutyrate (3HB) and 3-hydroxyvalerate (3HV). Modeling of SAXS results showed that the morphology of this isodimorphic system is better described by two phases, crystalline and amorphous, having defects within each domain. This is in contrast to a model with a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…When the 3HV comonomers are included in the P(3HB)type lattice, they will result in "less-perfect" crystals with more defects, smaller crystalline domains and less brittleness [215]. At higher HV contents the spherulites are small as the rate of crystallization is slower and/or there are relatively more nucleation sites.…”
Section: Isodimorphism In P(3hb-co-3hv) Copolymersmentioning
confidence: 99%
“…When the 3HV comonomers are included in the P(3HB)type lattice, they will result in "less-perfect" crystals with more defects, smaller crystalline domains and less brittleness [215]. At higher HV contents the spherulites are small as the rate of crystallization is slower and/or there are relatively more nucleation sites.…”
Section: Isodimorphism In P(3hb-co-3hv) Copolymersmentioning
confidence: 99%
“…In polyolefins such as isotactic polypropylene, defect sites are generated during the polymerization process, making it impossible to specify which monomer unit will become a defect site. For this reason, most studies of defect sites in polymers have used copolymers, in which the minor component in the copolymer corresponds to a defect site that can readily be identified in the NMR spectrum. However, defect sites in copolymers are constitutional defects, not configurational defects as found in stereoregular polymers . Another approach to study defect sites is to predict their chemical shifts based upon ab initio calculations and compare the simulated NMR spectrum to the experimental spectrum. , The presence of stereodefects is inferred by their effect on the line shape, but this method requires extensive deconvolution of the line shape into multiple peaks.…”
mentioning
confidence: 99%
“…The two monomers HB and HV are similar in chemical structure, and have the same chain conformation of the left‐handed 2 1 helix in orthorhombic unit cell . The occurrence of isomorphism in P(HB‐ co ‐HV) has been confirmed by wide‐angle X‐ray diffraction (WAXD), nuclear magnetic resonance (NMR), and infrared spectroscopy . Moreover, the crystallization behavior of P(HB‐ co ‐HV) was also affected dramatically by HV content.…”
Section: Introductionmentioning
confidence: 91%
“…In particular, it has been reported that both the unit cell parameters a and b enlarge with increasing HV content, for the ethyl side group of HV units expands both the planes perpendicular to chain axis . Further, both the percent of HV units in PHB crystals and the disorder of chain folding in crystalline phase increase with HV content . More importantly, the P(HB‐ co ‐HV) with HV content lower than 10 mol % reflects the similar morphological variation to that of PHB, but differs with those of HV content higher than 10 mol % .…”
Section: Introductionmentioning
confidence: 94%